OPTIMIZING READING COMPREHENSION IN VOCATIONAL HIGH SCHOOL PHASE F STUDENTS: THE ROLE OF VERBAL-LINGUISTIC INTELLIGENCE AND TEACHER COMPETENCE THROUGH THE UNDERSTANDING BY DESIGN APPROACH - Sugandi, Bastian; Eryon, Eryon; Kamiliya, Zainina (JOURNAL OF LANGUAGE, 2025)
Reading comprehension is a fundamental literacy skill that determines students’ academic success and readiness for the workforce. However, Indonesian students’ low performance in international assessments highlights the urgency of addressing reading literacy, particularly at the vocational high school level where learners are preparing for internships and direct entry into employment. This study examines the influence of verbal-linguistic intelligence and teacher competence, within the framework of the Understanding by Design (UbD) approach, on students’ reading comprehension, with learning motivation considered as a mediating variable. A quantitative research design was applied, involving 104 students from a Vocational High School (Phase F), selected using Slovin’s formula and simple random sampling. Data were collected through tests and questionnaires and analyzed using Structural Equation Modeling with the Partial Least Squares method. The findings demonstrate that both verbal-linguistic intelligence and teacher competence have a significant positive effect on learning motivation. These factors also showed a positive influence on reading comprehension, although their direct influence had weak significance. Importantly, learning motivation is confirmed as a strong mediator, strengthening the impact of teacher competence and verbal-linguistic intelligence on reading comprehension. This study underscores the importance of fostering students’ linguistic capacity and enhancing teacher competence through the UbD approach, as these efforts are more effective when supported by high learning motivation.